Kompetensi dan Disiplin Kerja Aparatur Terhadap Kualitas Pelayanan Publik Kecamatan Sidang Barang - Undang (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze and explain the influence of apparatus competence and work discipline on the quality of public services in Sidang Barang District. Public service represents a primary obligation of the state; however, fluctuations in service quality and human resource constraints often hinder the fulfillment of community needs. This research employed a quantitative explanatory approach involving 163 respondents consisting of neighborhood administrators (RW), civil servants (PNS), and government employees with work agreements (PPPK), selected using proportionate stratified random sampling. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that apparatus competence has a positive and significant effect on public service quality, with a path coefficient of 0.526 and a t-statistic value of 9.186. Similarly, work discipline shows a positive and significant effect, with a path coefficient of 0.461 and a t-statistic value of 8.005. Collectively, these variables contribute strongly, explaining 95.4% of the variance in public service quality, with a high predictive relevance (Q²) value of 0.640. In conclusion, strengthening knowledge, skills, and professional attitudes accompanied by adherence to work regulations is a key factor in creating reliable, responsive, and trustworthy bureaucratic services at the district level.